2014
DOI: 10.1109/tap.2014.2308516
|View full text |Cite
|
Sign up to set email alerts
|

Beam Tilting Antenna Using Integrated Metamaterial Loading

Abstract: This communication presents a technique to redirect the radiation beam from a planar antenna in a specific direction with the inclusion of metamaterial loading. The beam-tilting approach described here uses the phenomenon based on phase change resulting from an EM wave entering a medium of different refractive index. The metamaterial H-shaped unit-cell structure is configured to provide a high refractive index which was used to implement beam tilting in a bow-tie antenna. The fabricated unit-cell was first cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 14 publications
0
80
0
Order By: Relevance
“…The drawback of this configuration is its large physical size, i.e., , as it requires two lines of 26-element linear array and its sidelobe is 5 dB. Authors in [6] have demonstrated the beam-tilting phenomenon can be realized using high refractive-index metamaterial loading that is integrated within the antenna structure.…”
Section: Improvement Of Gain and Elevation Tilt Anglementioning
confidence: 99%
See 1 more Smart Citation
“…The drawback of this configuration is its large physical size, i.e., , as it requires two lines of 26-element linear array and its sidelobe is 5 dB. Authors in [6] have demonstrated the beam-tilting phenomenon can be realized using high refractive-index metamaterial loading that is integrated within the antenna structure.…”
Section: Improvement Of Gain and Elevation Tilt Anglementioning
confidence: 99%
“…2, is employed. This is a modified version of the H-shaped meandered-line metamaterial structure in [6]. The unit cell is constructed on a Rogers RT5880 substrate with the thickness ( ) of 0.508 mm, permittivity ( ) of 2.3, and loss tangent of 0.0009.…”
Section: Mechanism Of Beam-tiltingmentioning
confidence: 99%
“…It is widely used in different applications areas, such as sensors [4,5], energy harvesting [6], wave polarization [7,8], and controllable absorber [9]. It is also used for antennas performance enhancement, such as radiation enhancement [10], multi-directional beam generation [11], beam tilting [12][13][14], gain enhancement [15,17], bandwidth enhancement [15], directivity [16], and multiband operation [18]. In [4], a circular split ring resonator based on metamaterial, used for fluid, strain and rotation sensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…A pattern controlled frequency tunable microstrip antenna loaded with multiple split ring resonators using RF MEMS switches is presented to control the direction of the major lobe of the radiation pattern [12]. In [13], it is investigated that the integrated metamaterial loaded in a planar antenna can deflect the beam of an end-fire antenna by 17 • with respect to the end-fire direction in the frequency range of 7.3-7.5 GHz. An electronic bandgap structure integrated with the orthogonal plane of a dipole antenna [14] is presented for tilting the beam about 28 • at 3.5 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the authors in [10] integrated a 4×3 array of high refractive-index metamaterial unit-cells with a bow-tie antenna to demonstrate the feasibility of tilting the direction of the antenna main beam for C-band applications; however the refractive index of the unit-cell could not be altered. With this technique, the antenna exhibits again enhancement of 1.5-2.5 dBi over the frequency range of 7.3-7.7 GHz but the angle of the main beam is limited to 17 o .The authors in [11] presented passive fixed beam forming network (BFN) by applying a 4×4 Butler matrix consisting a SIW phase shifter and coupler to tilt the main beam in both E-and H-planes by 20 o .…”
mentioning
confidence: 99%